KETERGANTUNGAN EKONOMI MASYARAKAT PERBATASAN INDONESIA TERHADAP PRODUK MALAYSIA: KAJIAN PUSTAKA ATAS FAKTOR PENYEBAB DAN DAMPAKNYA - Muhammad Syafri; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
The economic dependence of Indonesian border communities on Malaysian products is a phenomenon influenced by various structural factors and policies. This study aims to identify the main contributing factors, such as geographical proximity, infrastructure limitations, differences in product prices and quality, as well as weak local economic development and Indonesian government intervention. This dependence has significant impacts on the socio-economic life of border communities, including reduced competitiveness of domestic products, changes in consumption patterns, increased social and economic vulnerability, and weakened national integration. The literature review indicates that efforts to strengthen the local economy, improve infrastructure, and implement cross-border policies that prioritise border communities are essential to reduce this dependence and reinforce Indonesia's position in this strategic region.